A clinical evaluation and acceptability study of the innovative SurePulse VS wireless heart rate monitor across the neonatal journey - Peterson, Jennifer; Jennings, Clare; Mahaveer, Ajit (Frontiers in Pediatrics, 2024)
Background The SurePulse VS device is an innovative wireless heart rate monitor designed for neonatal patients. This study evaluates the application of SurePulse VS technology in clinical practice. Methods Data were collected about the quantitative metrics of the device itself when deployed on real infants and qualitative feedback from perinatal professionals and parents regarding their experiences using this novel technology. Results This study recruited 101 infants and achieved target completion rates of 101 healthcare professional (HCP) and 51 parent questionnaires over the seven-month study period. The SurePulse device was deployed across a range of gestational ages (34–39 weeks) and birth weights (1.8 – 3.5kg). Device deployment was performed across a range of clinical environments, with 51% of deployments at delivery and 47% within the neonatal unit. The data show clinically acceptable timings from device deployment to heart rate signal acquisition (median 20 seconds (IQR 15-76 seconds)). HCP feedback rated SurePulse monitoring as “Always” or “Mostly” reliable in 80% of cases. Parental feedback reported that having the SurePulse device was reassuring, convenient and beneficial to them. These positive comments were reflected across device deployment in the delivery room and within the neonatal unit. Conclusions The study findings show that the SurePulse device has potential to be a significant advancement in the way neonatal patients are monitored in a variety of post-delivery circumstances. This study has demonstrated that the SurePulse device has utility throughout the neonatal journey, enabling accurate heart rate monitoring in a manner that promotes parent-infant contact and bonding.